Effects of vitamin C and vitamin E on lipid peroxidation, blood serum metabolites, and mineral concentrations of laying hens reared at high ambient temperature - Şahin, Kazım; Şahin, Nurhan; Yaralioglu, S (Springernature, 2002)
This study was conducted to determine the effects of vitamin C (L-ascorbic acid) and vitamin E (alpha-tocopherol acetate) on serum concentrations of lipid peroxidation (MDA) and triiodothyronine (T-3) thyroxine (T-4), adrenocorticotropic hormone (ACTH), and some metabolite and mineral in laying hens reared at high ambient temperatures ranging from 25degreesC to 35degreesC. One hundred twenty laying hens (18 wk old; Hy-Line) were divided into 4 groups, 30 hens per group. The laying hens were fed either a basal diet (control) or the basal diet supplemented with either 250 mg of L-ascorbic acid/kg of diet (vitamin C), 250 mg of alpha-tocopherol acetate/kg of diet (vitamin E), or 250 mg of L-ascorbic acid plus 250 mg alpha-tocopherol acetate/kg of diet (combination). Separately or as a combination vitamins C and E increased serum vitamin C and vitamin E concentrations (p < 0.001) but decreased serum MDA concentration (p < 0.05). Serum concentrations of vitamin E and vitamin C were found highest but serum MDA concentration was lowest in the combination group. Supplemental vitamins C and E either separately or in a combination increased serum T-3 and T-4 concentrations (p < 0.05), whereas decreased serum ACTH concentration (p < 0.01). Serum glucose and cholesterol concentrations decreased, whereas serum protein concentration increased (p < 0.05) when vitamins C and E singly or together were added to the diet. Vitamin C and vitamin E supplementation resulted in an increase in serum concentrations of Ca, P, and K (p < 0.01) but a decrease in serum concentration of Na (p < 0.05). The results of the present study suggest that supplemental vitamin C and vitamin E alter serum lipid peroxidation, vitamin C, vitamin E and metabolite status, and diets supplemented with a combination of these two vitamins offer a good management practice in laying hens reared at high temperatures. In addition, the results suggest that dietary vitamin C and vitamin E act synergistically.
Keywords: laying hen; heat stress; vitamin C; vitamin E; lipid peroxidation; thyroid; serum metabolites; minerals